SAMINISME DAN ISLAM JAWA - Huzer Apriansyah (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
Saminism as cultural identity and part of Indonesian plurality stillsurvives until today. Historically, Saminism was born as a cultural andpolitical reaction against colonialism but practically it was more aboutreligious way, in this point some religions in Java have been interactedwith saminism leaders and followers. Based on those facts it would beinteresting to understand how the relation between Islamic values andsaminism through socio-ethnography. On the other hand, how the historyof saminism related to political and social condition of Indonesia isalso interesting. Agama Adam or religion of Adam as a way on Saminismeis one of evidence that Islamic values connected with saminism.